Ethical Competence and Perioperative Nursing - Taylor, Carol (Operating Room Nurses Association of Canada Journal, 2001)
In this article an experienced nurse ethicist will lead readers in an exploration of the ethical challenges confronting perioperative nurses today. An argument will be made for ethical competence as a core competence for all health care professionals. After distinguishing ethical uncertainty, dilemma and distress, tools to facilitate moral reasoning and ethical decision making are outlined. Upon completion of this article, perioperative nurses will be able to: 1. Distinguish ethical uncertainty, ethical dilemma, and ethical distress. 2. Identify potential areas of conﬂict between professional and personal values. 3. Describe ethical competence as a core competence of professional nurses. 4. Apply moral reasoning and ethical decision making skills to ethical dilemmas.